Uncovering the hidden value of scarce resources: frugality, resourcefulness and innovative behavior among student entrepreneurs - Mario A. Manzi-Puertas; Izaskun Agirre-Aramburu; Sain López-Pérez (Cogent Business & Management)
Student entrepreneurs are key actors in innovation ecosystems, yet little is known about how they innovate under resource constraints. Drawing on the Social Cognitive Theory of Self-Regulation, this study explores the ways in which frugality influences innovative behavior through entrepreneurial bricolage, financial bootstrapping, and improvisation. Using PLS-SEM and Necessary Condition Analysis with data from 151 student entrepreneurs in higher education in Spain, the results show that frugality impacts innovative behavior only through the full mediation of entrepreneurial bricolage. Financial bootstrapping and improvisation also emerge as necessary conditions complementing this core relationship. This study contributes to the scholarship by: (1) providing a nuanced framework of entrepreneurial resourcefulness that reveals how cognitive traits are translated into innovative outcomes through specific behavioral mechanisms; (2) demonstrating how resourceful behaviors function simultaneously as both pathways and prerequisites at different achievement levels; and (3) introducing a graduated model of necessity that identifies the point at which specific capabilities become necessary for innovative behavior at different performance levels. These findings offer insights into the ways in which student entrepreneurs can develop both cognitive and behavioral resourceful mechanisms, and highlight the importance of building such mechanisms to support their innovative behavior.